The Roles of Internal Audit in Risk Management at Local Governments in West Java Province - Rosdini, Dini; K. Fitriyah, Fury; Yusi Sari, Prima; Irawady, Cahya (Opción)
One way to create clean, effective, democratic and trustworthy local governance is by raising the accountability of financial management. On the other hand, prob- lems have been found in the internal control of local governance (Audit Board of the Republic of Indonesia, 2016). The limitations of internal control consist of issues in the accounting and reporting control system, in the control system over the implementation of the income and expenditure budget, and in the internal con- trol structure. In local government activities, internal control functions are carried out by Government Internal Auditors. The strategic roles of Government Internal Auditors in the budget planning process by reviewing the budget and supporting documents exemplify quality assurance. The effectiveness of Government Inter- nal Auditors in performing risk management, control, and governance is expected to drive success in quality assurance. This research seeks to identify the roles of Government Internal Auditors at local governments in the province of West Java through a focus group discussion (FGD) and survey approach. The FGD and sur- vey were conducted on five local governments in West Java selected based on high, medium and low maturity levels. Results of the survey show the perception of respondents that Government Internal Auditors have been reasonably effective and so has risk management at the local governments. On the contrary, in-depth interviews revealed several obstacles that may hamper or decrease the effectiveness of Government Internal Auditors in applying risk management at local governments, namely lack of work- force, the competence of Government Internal Auditors, tone of the top, and challenges against independence.